Roles for Exosome in Various Kidney Diseases and Disorders - Thongboonkerd, Visith (Frontiers in Pharmacology, 2020)
Exosome is a nanoscale vesicle with a size range of 30-100 nm. It is secreted from cell to extracellular space by exocytosis after fusion of multivesicular body (MVB) (formed by endocytic vesicles) with plasma membrane. Exosome plays several important roles in cellular homeostasis and intercellular communications. During the last two decades, exosome has acquired a wide attention to explore its additional roles in various aspects of cell biology and function in several organ systems. For the kidney, several lines of evidence have demonstrated that exosome is involved in the renal physiology and pathogenic mechanisms of various kidney diseases/disorders. This article summarizes roles of the exosome as the potential source of biomarkers, pathogenic molecules and therapeutic biologics that have been extensively investigated in many kidney diseases/disorders, including lupus nephritis (LN), other glomerular diseases, acute kidney injury (AKI), diabetic nephropathy (DN), as well as in the process of renal fibrosis and chronic kidney disease (CKD) progression, in addition to polycystic kidney disease (PKD), kidney transplantation, and renal cell carcinoma (RCC). Moreover, the most recent evidence has shown its emerging role in kidney stone disease (or nephrolithiasis), involving inflammasome activation and inflammatory cascade frequently found in kidney stone pathogenesis.